ANEMIA IN ELDERLY PATIENTS IN GENERAL MEDICAL PRACTICE: CURRENT APPROACHES TO DIAGNOSIS AND TREATMENT - T. Yu. Kalyuta; O. A. Kazhekin; O. A. Soldatova (Вестник медицинского института «Реавиз»: Реабилитация, врач и здоровье, 2021)
Anemia was considered one of the epidemics of the twentieth century. Anemia demonstrated its negative impact on the prognosis in many clinical conditions. One in three patients seen by a general practitioner has anemia.  Currently available guidelines on the diagnosis and treatment of anemia do not consider its polymorbidity in elderly  patients, as well as the negative impact of some therapeutic tactics (such as aggressive iron therapy, blood transfusion) on the prognosis. On the other hand, anemia often remains untreated. Since anemia is a modifiable risk factor in elderly patients, further studies aimed at the development of integrated treatment approaches with the consideration of polymorbidity and high prevalence of polyvalent anemia in these patients are highly relevant.